Pengaruh Media Pembelajaran Berbasis TIK Terhadap Motivasi dan Hasil Belajar IPA Siswa Kelas V SDN Model Terpadu Madani Palu - Halidi, Hasan Mahmud; Husain, Sarjan N.; Saehana, Sahrul (Universitas Tadulako, 2015)
This study tries to describe the influence of ICT media toward student’s motivation and learning outcome.The study question was how to ICT media influences toward student’s motivation and learning outcome.This study was carried out at SDN Model Terpadu Madani Palu on even semester 2013-2014. The methods of this study was experiment by using ICT media as dependent variable (X). Motivation and learning outcomes as independent variable (Y). The result of this study by using F-test were both the motivation and learning outcome very significant. The result of Fcount motivation and learning outcome each by 242.07 and 121.00. This result more than Ftable (1%) = 94.40. In conclusion: By using ICT media on science learning at grade 5th SDN Model Terpadu Madani Palu would be increasing ofstudent’s motivation and learning outcome.